Sustenance Trial to Analyze the Effects of Black Soldier Fly Larvae Meal on the Reproductive Efficiency of Sows and the Hematological Properties of Suckling and Weaning Piglets - Kiyonori Kawasaki; Junliang Zhao; Natsu Takao; Masaki Sato; Takuma Ban; Kaoru Tamamaki; Masanori Kagami; Kiminobu Yano (Animals, 2023)
The escalating demand for meat, driven by global population growth, necessitates sustainable solutions for animal feed production. This study investigated the effects of substituting conventional protein resources in sow and piglet dietary regimens with black soldier fly (BSF; Hermetia illucens) meal on reproductive efficiency, blood profile, piglet growth, and intestinal tissue morphology. The results indicate that substituting animal-derived and soy proteins with BSF meal does not compromise sow reproductive performance. Although no notable disparities were observed in piglet growth, the feed conversion ratio from the 28- to 35-day age marks were lower in the BSF-fed groups. This suggests that the animal protein-BSF substitution rate may require optimization, potentially involving chitin removal from BSF meal to enhance digestibility. Minor variations in the hematological composition and properties in piglets, with elevated high-density lipoprotein cholesterol levels in the high BSF group at the 28-day mark, were potentially attributable to the unique fatty acid composition of BSF meal. Moreover, this study potentiates future exploration into the efficacy of complete animal protein substitution with BSF meals on piglet nutrition and physiology, particularly in fattening pigs. The practical implementation of BSF meals in animal feed production holds promise for enhancing the sustainability of the swine industry.